Feeding, Communication, Hydrocephalus, and Intracranial Hypertension in Patients With Severe FGFR2-Associated Pfeiffer Syndrome. Issue 1 (January 2021) - Kilcoyne, Sarah; Potter, Katherine Ruth; Gordon, Zoe; Overton, Sarah; Brockbank, Sally; Jayamohan, Jayaratnam; Magdum, Shailendra; Smith, Martin; Johnson, David; Wall, Steven; Wilkie, Andrew O.M.
Abstract : Background: Pfeiffer syndrome is associated with a genetic mutation of the FGFR2 (or more rarely, FGFR1 ) gene, and features the combination of craniosynostosis, midface hypoplasia, broad thumbs and broad great toes. Previous research has identified a wide spectrum of clinical phenotypes in patients with Pfeiffer syndrome. This study aimed to investigate the multifactorial considerations for speech, language, hearing and feeding development in patients with severe genetically-confirmed Pfeiffer syndrome. Methods: A 23-year retrospective case-note review of patients attending the Oxford Craniofacial Unit was undertaken. Patients were categorized according to genotype. Patients with mutations located in FGFR1, or outside the FGFR2 IgIII domain-hotspot, or representing known Crouzon/Pfeiffer overlap substitutions were excluded. Twelve patients with severe FGFR2 -associated Pfeiffer syndrome were identified. Results: Patients most commonly had pansynostosis (n = 8) followed by bicoronal (n = 3), and bicoronal and sagittal synostosis (n = 1). Seven patients had a Chiari I malformation. Four patients had a diagnosis of epilepsy. Ten patients had with hydrocephalus necessitating ventriculoperitoneal shunt insertion. Feeding difficulties were common (n = 10/12) and multifactorial. In 5/12 cases, they were associated with pansynostosis, hydrocephalus, tracheostomy and tube feeding in infancy. Hearing data were available for 10 patients, of whom 9 had conductive hearing loss, and 8 required hearing aids. Results indicated that 3/4 patients had expressive language difficulties, 3/4 had appropriate receptive language skills. 6/12 patients had a speech sound disorder and abnormal resonance. Conclusion: This study has identified important speech, language, hearing and feeding issues in patients with severe FGFR2 -associated Pfeiffer syndrome. Results indicate that a high rate of motor-based oral stage feeding difficulties, and pharyngeal stage swallowing difficulties necessitating regular review by specialist craniofacial speech and language therapists Abstract : Supplemental Digital Content is available in the text